Percutaneous Radio-frequency Assisted Liver Partition with Portal vein embolization in Staged liver resection (PRALPPS) in patients with perihilar and intrahepatic cholangiocarcinoma: evaluation of short-term results - O. V. Melekhina; M. G. Efanov; R. B. Alikhanov; V. V. Tsvirkun; Yu. V. Kulezneva; I. V. Kazakov; P. P. Kim; A. N. Vankovich (Вестник хирургии имени И.И. Грекова)
Objective. To estimate the short-term results of modified variant of ALPPS (PRALPPS) in patients with perihilar and intrahepatic cholangiocarcinoma.Material and methods. Procedure was indicated for future liver remnant <40%.Results. PRALPPS was applied in 13 patients and completed in 10 patients. Degree of hypertrophy and kinetic growth rate were 48 and 4.3%/day respectively. Major morbidity (>II) after the stage 1 and 2 was presented in 3 (only IIIa) and 7 patients, respectively.Conclusion. PRALPPS may be considered as an effective and safe procedure in patients with perihilar and intrahepatic cholangiocarcinoma.